A degenerate telomerase RNA directs telomeric DNA synthesis in lepidopteran insects - Yah-Huei Chou; Dhenugen Logeswaran; Chi-Nga Chow; Pamela Dunn; Joshua D. Podlevsky; Tianxiang Liu; Khadiza Akhter; Julian J.‐L. Chen (2025)
Telomerase elongates telomeres to maintain chromosome stability in most eukaryotes. Despite extensive studies across eukaryotic kingdoms, the telomerase holoenzyme in arthropods remains poorly understood. In this study, we purify the telomerase ribonucleoprotein complex from the lepidopteran insect Spodoptera frugiperda (fall armyworm) and identify a copurified 135-nucleotide telomerase RNA (TR) component. This miniature S. frugiperda TR (sfTR), the smallest TR known to date, retains a universal pseudoknot structure and a structurally defined template. Despite its small size, sfTR assembles with the recombinant S. frugiperda telomerase reverse transcriptase (sfTERT) protein in vivo to reconstitute telomerase activity for the synthesis of insect telomeric DNA repeats (TTAGG)n. The sfTR gene, like other animal TR genes, features an snRNA-type RNA polymerase II promoter. Uniquely, the sfTR transcript harbors a 5′-7-methylguanosine (M 7 G) cap, as opposed to the more typical snRNA-type 2,2,7-trimethylguanosine (TMG) cap. The difference in 5′-cap is likely because sfTR lacks the H/ACA snoRNA biogenesis domain necessary for cap hypermethylation. Moreover, sfTR also lacks the CR4/5 regulatory domain that is indispensable in vertebrate TRs for telomerase activity. This degenerate sfTR complements an enigmatic sfTERT that is missing certain telomerase-specific elements yet catalytically active in the absence of sfTR. Thus, insects have evolved a simplified telomerase, consisting of a small noncoding RNA that retains only minimal attributes essential for telomerase function. The simplified insect telomerase demonstrates a plausible evolutionary pathway for the emergence of telomerase ribonucleoprotein complex, arising from an ancient reverse transcriptase associated with a simple templating RNA component in early eukaryotes.